Synergizing Food Security, Digitalization, and Community Empowerment through Educational Agro-Ecotourism - Ilham Nur Hanifan Maulana; Ahmad Herlyasa Sosro Pratama; Ginanjar Indra Kusuma Nugraha; Lydia Graceanova Wahyudi; Linda Putri Karunia Effendi (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Educational agro-ecotourism has emerged as an innovative strategy to integrate food security, economic value-added, and digitalization within community-based development. The community service program at Pleret Dam 1904 was conducted through nine structured stages, including modern agricultural training, post-harvest processing, institutional strengthening, and digital promotion activation. The program resulted in a 200 m² educational garden, three ready-to-market processed products, and improved governance capacity of the Tourism Awareness Group (Pokdarwis) through basic SOPs and bookkeeping. These findings confirm previous studies emphasizing the role of social capital and technological innovation in sustaining community-based ecotourism. The main contribution of this study lies in demonstrating that the synergy of educational agriculture, downstreaming, and digital promotion can serve as both a conceptual framework and a practical model for community empowerment. The implications are closely aligned with national and global agendas, particularly SDGs 2, 8, and 11, and provide opportunities for replication in other destinations with similar characteristics.